Effect of Rest Interval Between Sets in the Muscle Function During a Sequence of Strength Training Exercises for the Upper Body. Issue 6 (June 2021) - Matos, Filipe; Ferreira, Bruna; Guedes, Joana; Saavedra, Francisco; Reis, Victor M.; Vilaça-Alves, José
Abstract : Abstract: Matos, F, Ferreira, B, Guedes, J, Saavedra, F, Reis, VM, and Vilaça-Alves, J. Effect of rest interval between sets in the muscle function during a sequence of strength training exercises for the upper body. J Strength Cond Res 35(6): 1628–1635, 2021—The objective of this study was to observe the ideal recovery time between sets and exercises, for both chest and back, which allowed for maintaining muscle function with the initial load previously established. Sixty young men recreationally trained in strength training (ST) were divided into 2 groups: (a) 30 subjects were included in the GC group (the group that performed ST for the chest) and (b) 30 subjects were included in the GB group (the group that performed ST for the back). Each group was submitted to 3 experimental sessions, performing an ST sequence with 3 sets of 8 repetition maximum: GC performed a chest barbell press (CBP), an inclined CBP, and a chest butterfly; GB performed a lat pull-down, a back row, and a shoulder extension on the high pulley. The experimental sessions differed in rest time between sets performed (60, 90, and 120 seconds). For both groups in each sequence, significantly higher numbers of repetitions were observed with the rest time of 120 seconds relative to the rest time of 90 seconds ( p = 0.004), 120 seconds in relation to the rest time of 60 seconds ( p = 0.001), and in the rest interval of 90 seconds in relation to the rest time of 60 seconds ( p < 0.0001). The results showed that 120 seconds was sufficient to maintain muscle function and perform the total number of repetitions per set. The data seem to show that for the ST methodology applied, it is not appropriate to assume that a certain relative intensity will translate into a similar number of repetitions in different exercises, especially with shorter rest intervals such as 60 and 90 seconds.